PEMBIAYAAN QARDHUL HASAN PADA PRODUK SUPER MIKRO BANK ACEH SYARIAH CABANG BANDA ACEH: STUDI FIQH MUAMALAH - Qaulan Maisura; Edi Yuhermansyah; Husni Abdul Jalil (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2024)
This research aims to examine the implementation of the qardhul hasan contract at Bank Aceh Syariah. To obtain data, the author used a qualitative research method, with an empirical juridical approach where the main source was obtained from interviews with stakeholders. Meanwhile, secondary data was obtained from reading sources such as books, journals, articles and other sources related to this research topic. The research results show that one of the financing schemes with a qardhul hasan agreement is intended for super micro businesses, where the maximum financing amount is IDR 10,000,000.00. Super micro financing is different from other financing schemes, where the creditor does not require collateral (collateral) for the debtor. Apart from that, Bank Aceh Syariah Banda Aceh Branch with a maximum financing agreement period of 3 years. In qardhul hasan financing, the administration fee charged to the customer is 1% of the financing amount. In general, the author can conclude that this financing scheme is in accordance with DSN-MUI Fatwa No.19/DSN-MUI/IX/2001, however based on Muamalah Fiqh it is permissible because the use of non-halal fund income is one of the sources of funds in its implementation.